High rate of faecal carriage of extended-spectrum β-lactamase-producing Enterobacteriaceae in healthy children in Bangui, Central African Republic. (October 2016) - Farra, A.; Frank, T.; Tondeur, L.; Bata, P.; Gody, J.C.; Onambele, M.; Rafaï, C.; Vray, M.; Breurec, S.
Abstract: The aim of this study was to estimate the prevalence of extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-E) in faeces of healthy children aged 0–59 months in Bangui (Central African Republic). Stool samples of 134 children, recruited for a matched case-control study, were cultured on a commercial ESBL-selective chromogenic medium (CHROMagar ESBL, France). The phenotypic resistance patterns of isolated strains were investigated, as well as the genetic basis for antibiotic resistance. The factors associated with increased risk for ESBL-E carriage were also studied. The prevalence of ESBL-E carriage was 59% (79/134), one of the highest reported worldwide. The only factor found to be associated with carriage was living in a highest-income family ( p =0.03). In all, 83 ESBL-E were recovered as simultaneous carriage of two strains was detected in four children. bla CTX-M-15 was found in all strains except two, frequently associated with qnr (54/81, 66%) and aac (6′)- Ib-cr (35/81, 43%) genes. Escherichia coli, the most commonly recovered species (51/83, 61%), was assigned mainly to the pandemic B2-O25b-ST131 group (39/51, 76%). Resistance transfer, which was studied in 20 randomly selected ESBL-E strains, was successful in 13 (13/20, 65%) isolates. In eight of these isolates (8/13, 62%), bla CTX-M-15 genes were found in incompatibility group FIb conjugative plasmids. We found one of the highest prevalence rates of faecal carriage of ESBL-E reported worldwide, highlighting the need to improve control of the distribution of antibiotics in limited-resource countries.